2013
DOI: 10.4236/ijoc.2013.33a001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthetic Method for the Vilsmeier-Haack Reagent and Green Routes to Acid Chlorides, Alkyl Formates, and Alkyl Chlorides

Abstract: An environmentally benign and practical preparation method for the Vilsmeier-Haack reagent (VH) has been developed by using phthaloyl dichloride with DMF in toluene or 2-chlorotoluene. Phthalic anhydride as the byproduct was recovered in high yield by simple filtration. Some aromatic acids have been transformed into the corresponding acid chlorides in good yields by employing the isolated VH. Treatment of primary or secondary alcohols with VH gave alkyl formates or alkyl chlorides by depending on the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…As an explanation of the fast activation of 21a/b in the presence of NMP, in contrast to the very slow chlorination reaction in absence of NMP, we considered the catalytic activity of NMP, as evidenced by the fast activation of 21a/b when NMP was added to the reaction mixture, and therefore we propose the mechanism in Scheme 5 B. Although the proposed mechanism has not yet been clarified, NMP has been proposed as a catalyst for the reaction of carboxylic acids with SOCl 2 , possibly through the formation of 23 , leading to the Vilsmeier complex 24 and/or 26 [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Thus, the reaction of 23 and/or 26 with 21a/b would form 27 , while the reaction of 24 with 21a/b would give 25 .…”
Section: Resultsmentioning
confidence: 99%
“…As an explanation of the fast activation of 21a/b in the presence of NMP, in contrast to the very slow chlorination reaction in absence of NMP, we considered the catalytic activity of NMP, as evidenced by the fast activation of 21a/b when NMP was added to the reaction mixture, and therefore we propose the mechanism in Scheme 5 B. Although the proposed mechanism has not yet been clarified, NMP has been proposed as a catalyst for the reaction of carboxylic acids with SOCl 2 , possibly through the formation of 23 , leading to the Vilsmeier complex 24 and/or 26 [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Thus, the reaction of 23 and/or 26 with 21a/b would form 27 , while the reaction of 24 with 21a/b would give 25 .…”
Section: Resultsmentioning
confidence: 99%
“…VR (colorless solid, 660.0 mg, 5.15 mmol) was added to a stirred solution of methyl 1 H -pyrrole-2-carboxylate 1b (401.8 mg, 3.21 mmol) in dry CHCl 3 (11 mL) at 0 °C, and the resulting mixture was stirred at room temperature for 5.5 h. GC analysis showed that 1b was completely consumed and that the 2b / 3b ratio was <0.1/>99.9. The mixture was neutralized with sat.…”
Section: Methodsmentioning
confidence: 99%
“…VR is usually prepared from N , N -dimethylformamide (DMF) and phosphoryl trichloride (POCl 3 ) and used in situ without isolation. We recently developed new preparations of VR (Scheme ) using phthaloyl dichloride . This method avoids the production of wastewater containing phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lower molecular weight of chloride, when compared to other halogens, substitution of chloride generates less waste . Unfortunately, synthesis of chlorides from alcohols requires highly toxic and waste-intensive chlorinating agents such as thionyl chloride, phosphorus chlorides, pivaloyl chloride, Vilsmeier reagent, tosyl chloride, 2,4,6-trichloro-[1,3,5]­triazine with DMF, oxalyl chloride, and phosgene . Mostly, chlorinating agents are used in stoichiometric or excessive amounts that lead to a high generation of waste …”
Section: Introductionmentioning
confidence: 99%